An elastic-plastic stress analysis in a thermoplastic composite cantilever beam loaded uniformly - Sayman, O; Arslan, N; Pihtili, H (Sage Publications Ltd, 2001)
In this study an elastic-plastic stress analysis is carried out on a steel fiber reinforced thermoplastic composite cantilever beam loaded uniformly at the upper surface. An analytical solution is found satisfying both the governing differential equation in two dimensional case and boundary conditions. In this solution, the intensity of the uniform force is chosen small, therefore the transversely normal stress component is neglected in comparison with the other stress components. The thermoplastic matrix is reinforced unidirectional ly by steel fibers. The orientation angles of the fibers are chosen as 0 degrees, 30 degrees, 45 degrees, 60 degrees and 90 degrees. The plastic region begins first at the upper surface of the beam for 30 degrees and 45 degrees orientation angles. However, it starts earlier at the lower surface for 60 degrees orientation angle. The intensity of the normal residual stress component in the axial direction of the beam is maximum at the upper and/or lower surfaces in the beam. The intensity of the shear residual stress is maximum on or around the axial axis of the beam.
Keywords: Finite-Element-Analysis; Residual-Stresses; Plates